2023
DOI: 10.1002/anie.202313389
|View full text |Cite
|
Sign up to set email alerts
|

Significant Roles of Surface Hydrides in Enhancing the Performance of Cu/BaTiO2.8H0.2 Catalyst for CO2 Hydrogenation to Methanol

Yang He,
Yuanyuan Li,
Ming Lei
et al.

Abstract: Tuning the anionic site of catalyst supports can impact reaction pathways by creating active sites on the support or influencing metal‐support interactions when using supported metal nanoparticles. This study focuses on CO2 hydrogenation over supported Cu nanoparticles, revealing a 3‐fold increase in methanol yield when replacing oxygen anions with hydrides in the perovskite support (Cu/BaTiO2.8H0.2 yields ~146 mg/h/gCu vs. Cu/BaTiO3 yields ~50 mg/h/gCu). The contrast suggests that significant roles are played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Meanwhile, in situ DRIFTS results showed that the trend of CO species formation and decay was highly consistent with the trend of surface CO 2 . Considering that the trend of CO species formation and decay was significantly different from that of CH 4 , we believed that CO did not participate in the RDS generated by CH 4 . ,, According to previous reports, in the carbonyl pathway, the hydrogenation of CO was the RDS of the reaction . Therefore, the carbonyl pathway was not the main reaction pathway for the CO 2 hydrogenation on Ru/CPO-10.…”
Section: Resultsmentioning
confidence: 94%
“…Meanwhile, in situ DRIFTS results showed that the trend of CO species formation and decay was highly consistent with the trend of surface CO 2 . Considering that the trend of CO species formation and decay was significantly different from that of CH 4 , we believed that CO did not participate in the RDS generated by CH 4 . ,, According to previous reports, in the carbonyl pathway, the hydrogenation of CO was the RDS of the reaction . Therefore, the carbonyl pathway was not the main reaction pathway for the CO 2 hydrogenation on Ru/CPO-10.…”
Section: Resultsmentioning
confidence: 94%